Experimental and Theoretical Studies of Black Cumin Seed (Nigella sativa) Extract as Corrosion Inhibitor for ASTM A36 Steel - Yunia Maulida; Saprini Hamdiani; Sudirman Sudirman; Saprizal Hadisaputra (Jurnal Penelitian Pendidikan IPA, 2024)
Black cumin seed extract (Nigella sativa) is effective to control ASTM A36 steel corrosion in 1 M HCl solution. This study analyzed black cumin seed (BCS) extract as a corrosion inhibitor (0 to 500 ppm) by electrochemical method including Potentiodynamic Polarization (PDP) and Electrochemical Impedance Spectroscopy (EIS). The results revealed that with the PDP method the highest inhibition efficiency (IE) was 84.26% at the concentration of 500 ppm, and with the EIS method the IE value was 77.77% at the same concentration. The components of the extract were analyzed by GCMS and obtained major compounds are linoleic acid (22.12%), methyl linoleate (22.70%), 4-cyclopentene-1,3-dione,4-3-methyl-2-butenyl) (7.64%), methyl palmitate (6.66%), and palmitic acid (5.14%). A theoretical approach with computation was also carried out to investigate the performance and interaction of the major compounds in the BCS extract that a significant role as inhibitor. This was using Density Functional Theory (DFT) method and Monte Carlo simulation. The results showed that methyl linoleate compound as the most significant role.